Kecerdasan Emosional dan Kemampuan Adaptasi sebagai Determinan Kinerja Karyawan Generasi Z pada Industri Manufaktur - Zenit Tursina; Danny Ramdani; Salim Siregar (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the influence of emotional intelligence and adaptability on the performance of Generation Z employees in the manufacturing industry in Karawang Regency. The study employs a quantitative approach utilizing descriptive methods and multiple linear regression analysis processed via SPSS. The study population consists of 76,363 Generation Z employees working in the manufacturing industry in Karawang Regency. The sample was determined using a non-probability sampling technique with a purposive sampling approach. Based on Slovin's formula, a sample of 400 respondents was obtained. The analysis results indicate that emotional intelligence and adaptability simultaneously have a positive and significant effect on employee performance, evidenced by an F-calculated value of 144.254 exceeding the F-table value of 3.02 at a significance level of 0.000 (<0.05). Furthermore, the coefficient of determination test yielded an R² value of 0.421, meaning that emotional intelligence and adaptability collectively explain 42.1% of the variation in employee performance, while the remaining 57.9% is influenced by factors outside the research model. These findings demonstrate that enhancing emotional intelligence and adaptability is a crucial factor in boosting the performance of Generation Z employees in the manufacturing industry.